Respiratory Tract Infections and Antibiotic Resistance: A Protective Role for Vitamin D? - Derbyshire, Emma J.; Calder, Philip C. (Frontiers in Nutrition, 2021)
Upper and lower respiratory tract infections are amongst the most common infections globally, and in the United Kingdom they account for about half of all oral antibiotics prescribed. Antibiotic overuse and the emergence of “superbugs” that are resistant to their effects is a global problem that is becoming a serious concern. Considering this, the potential role of immunonutrition as a “prehabilitation” in helping to tackle bacterial infections and reduce over-reliance on antibiotic usage is gaining interest. This narrative mini review summarizes current knowledge on the roles of certain nutrients in helping to modulate immune function, with particular focus on vitamin D. Vitamin D supplementation appears to reduce the risk of acute respiratory tract infections and thus could have a valuable to play in reducing over reliance on antibiotics. Investment in high-quality trials is needed to further explore this field.